An analytically formulated structural strain method for fatigue evaluation of welded components incorporating nonlinear hardening effects - Pei, Xianjun; Dong, Pingsha (Fatigue & Fracture of Engineering Materials & Structures, 2019)
An analytically formulated structural strain method is presented for performing fatigue evaluation of welded components by incorporating nonlinear material hardening effects by means of a modified Ramberg‐Osgood power law hardening model. The modified Ramberg‐Osgood model enables a consistent partitioning of elastic and plastic strain increments during both loading and unloading. For supporting 2 major forms of welded structures in practice, the new method is applied for computing structural strain defined with respect to a through‐thickness section in plate structures and cross section in piping systems. In both cases, the structural strain is formulated as the linearly deformation gradient on their respective cross sections, consistent with the “plane sections remain plane” assumption in structural mechanics. The structural strain‐based fatigue parameter is proposed and has been shown effective in correlating some well‐known low‐cycle and high‐cycle fatigue test data, ranging from gusset‐to‐plate welded plate connections to pipe girth welds. Peer Reviewed https://deepblue.lib.umich.edu/bitstream/2027.42/146966/1/ffe12900.pdf https://deepblue.lib.umich.edu/bitstream/2027.42/146966/2/ffe12900_am.pdf